2020
DOI: 10.1002/adfm.201908855
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Based Porous Microcapsules as Bacterial Traps

Abstract: Exposure to live bacteria and accumulation of dead bacteria during bactericidal processes can cause bacterial infectious diseases, implant failure, and antibacterial surface deterioration. Microcapsules with asymmetrically distributed, funnel-shaped pores, which are capable of capturing, retaining, and killing bacteria are developed, offering a solution to bacterial contamination in liquids. It is found that bacterial isolation inside microcapsules is mainly driven by the bacteria's own motility and the microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Royal Society of Chemistry. (B) Porous particles for trapping bacteria 59 . Reprinted with permission from Reference 59.…”
Section: Biomedical Applications Of Polymer Microspheres With Surface...mentioning
confidence: 99%
See 1 more Smart Citation
“…Royal Society of Chemistry. (B) Porous particles for trapping bacteria 59 . Reprinted with permission from Reference 59.…”
Section: Biomedical Applications Of Polymer Microspheres With Surface...mentioning
confidence: 99%
“…Additionally, porous PLGA microcapsules can be used as bacterial traps, in which pores provide channels for bacteria to enter microcapsules (Figure 9B). 59 By using E . coli as a typical bacteria, Spatz et al found that E .…”
Section: Biomedical Applications Of Polymer Microspheres With Surface...mentioning
confidence: 99%
“…The asymmetric porous geometry in combination with the bacteria's own motility greatly diminishes the need for nutrient source or chemical components to entice the bacteria, thus reducing bacterial toxicity to surrounding cells. This device has shown great promises as an alternative to reduce bacterial contamination in liquids for environmental studies [42].…”
Section: Droplet Microfluidic Technology and Chemical Phase Separation Processmentioning
confidence: 99%
“…Die Mikrokapseln schirmen Bakterien und bakterielle Toxine ab. 19) Ein 39) Bei polymerbasierten Solarzellen haben nicht-Fulleren-basierte Akzeptormoleküle neuen Schub gebracht. Nehers Gruppe etwa hat nahezu barrierefreies photoinduziertes Entstehen freier Ladungsträger nachgewiesen.…”
Section: Wissenschaft + Forschungunclassified